ATP-dependent transporters: emerging players at the crossroads of immunity and metabolism - Balasubramanian, Akshaya; Sundrud, Mark S. (Frontiers in Immunology, 2023)
Nearly 50 ATP-binding cassette (ABC) transporters are encoded by mammalian genomes. These transporters are characterized by conserved nucleotide-binding and hydrolysis (i.e., ATPase) domains, and power directional transport of diverse substrate classes -ions, small molecule metabolites, xenobiotics, hydrophobic drugs, and even polypeptides -into or out of cells or subcellular organelles. Although immunological functions of ABC transporters are only beginning to be unraveled, emerging literature suggests these proteins have under-appreciated roles in the development and function of T lymphocytes, including many of the key effector, memory and regulatory subsets that arise during responses to infection, inflammation or cancers. One transporter in particular, MDR1 (Multidrug resistance-1; encoded by the ABCB1 locus in humans), has taken center stage as a novel player in immune regulation. Although MDR1 remains widely viewed as a simple drug efflux pump in tumor cells, recent evidence suggests that this transporter fills key endogenous roles in enforcing metabolic fitness of activated CD4 and CD8 T cells. Here, we summarize current understanding of the physiological functions of ABC transporters in immune regulation, with a focus on the anti-oxidant functions of MDR1 that may shape both the magnitude and repertoires of antigen-specific effector and memory T cell compartments. While much remains to be learned about the functions of ABC transporters in immunobiology, it is already clear that they represent fertile new ground, both for the definition of novel immunometabolic pathways, and for the discovery of new drug targets that could be leveraged to optimize immune responses to vaccines and cancer immunotherapies.